2009
DOI: 10.1016/j.compositesa.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of specimen thickness on the shock propagation along the in-fibre direction of an aerospace-grade CFRP laminate

Abstract: In-fibre measurements of the Hugoniot have been carried out on a carbon-fibrereinforced-polymer composite. For this material, we have shown at high shock stresses, a two component wave was formed consisting of a fast moving ramped portion and a slower moving shock wave. Changing the thickness of test specimen for a given shock stress resulted in a change in the magnitude and duration of the ramped portion of the wave front. As the shock stress imparted to the target was reduced, or the thickness of the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The density of the CFRP material, measured using a Micrometrics AccuPyc 1330 gas pycnometer, was 1.512 g/cc ± 0.001 g/cc. The dynamic behaviour of this type of laminate subjected to flyer-plate testing has been reported both by Millett et al [12] and ourselves [13]. The mass fraction of the reinforcement was measured using the acid digestion method according to ASTM D 3171-6, Procedure B.…”
Section: Materials Usedmentioning
confidence: 99%
“…The density of the CFRP material, measured using a Micrometrics AccuPyc 1330 gas pycnometer, was 1.512 g/cc ± 0.001 g/cc. The dynamic behaviour of this type of laminate subjected to flyer-plate testing has been reported both by Millett et al [12] and ourselves [13]. The mass fraction of the reinforcement was measured using the acid digestion method according to ASTM D 3171-6, Procedure B.…”
Section: Materials Usedmentioning
confidence: 99%
“…Millett et al also found that both orientations converged at higher values of u p . Hazell et al [2] investigated the in fiber shock propagation (fibers perpendicular to the shock front) and also found at higher stresses similar spatial separation of the propagating shock was seen. TWCP sample, similar to the one investigated here except with the weave angled at 20 • to the impact surface, was investigated by Burrell et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…The SATAC research program (Shock Adhesion Test for Adhesively Bonded Composites) aims to study the composites behaviour at very high strain rate in order to test their adhesion [15][16][17]. Other studies describe the behaviour of CFRP laminates under plate impact in the through-thickness direction [18], and along the fibre direction [19,20]. The response of glass fibers reinforced epoxy [21,22] Kevlar/epoxy and Spectra/epoxy composites [23] to a planar impact has also been investigated.…”
mentioning
confidence: 99%